PREPARATION AND CHARACTERIZATION OF HYDROXYAPATITE BIOCERAMIC BY HYDROTHERMAL METHOD - MUSTAFA, HIMDAD IBTRAHIM (Fırat Üniveristesi, 2017)
Bu yüksek lisans çalışmasında, hidrotermal metot ile hidroksiapatit (HAP) üretidi. Üretilen HAP numunesinin karakterizasyonu için yapısal analiz, termal analiz ve I-V HAP örneğinin özellikleri incelendiğinde, kristal yapısının elektrik iletkenliğinin 1.2x10-10 S / cm olduğu saptanmıştır. analizi yapıldı. Yapısal analizler difraksiyon veren düzlemleri belirlemek ve yüzey morfolojisini incelemek için yapıldı. Sıcaklığa bağlı kütle kaybını belirlemek ve faz geçişleri yada bozunmayı gözlemlemek için termal analiz oda sıcaklığından 925 ?C ye kadar yapıldı. Malzemenin elektriksel iletkenliğini belirlemek için Termal kararlılığı belirlemek için TGA-DA analizi yapıldı. Bileşim analizi EDX ile yapıldı. I-V karakterizasyonu yapıldı. Anahtar Kelimeler: Hidroksiapatit (HAP), hidrotermal metod, elektriksel iletkenlik.

In this master thesis, we prepared hydroxyapatite (HAP) by hydrothermal method. The structural analysis, thermal analysis and electrical characteristics of HAP sample have been investigated. The structural analysis was performed to determine the crystal structure electrical conductivity of the sample was obtained to be1.2x10-10 S/cm, and to observe the surface morphology of the sample. The thermal analysis was made from room temperature to 925 ?C, to determine the mass loss according to temperature and phase transitions or decomposition in the sample. TG-DTA analysis was done to determine the thermal stability. The compositional analysis was done by EDX. I-V analysis was made to calculate the electrical conductivity value of the sample. Keywords: Hydroxyapatite (HAP), hydrothermal method, electrical conductivity.
Keywords: Fizik ve Fizik Mühendisliği